Distributed Precoder Design Under Per-Small Cell Power Constraint - Roper, Maik; Svedman, Patrick; Dekorsy, Armin (2018 IEEE 88th Vehicular Technology Conference (VTC-Fall), 2018)
In this paper, a novel distributed precoding (DiP) algorithm for ultra-dense small cell (SC) networks is developed, where the SCs cooperate to perform a joint transmission to users (UEs) with limited and individual transmit powers. Different to most state of the art (SotA) DiP algorithms, the proposed precoder design is based on the assumption that each SC has only local channel state information (CSI) available. Additionally, there are no constraints on the number of antennas for each SC, but only one constraint on the sum of all transmit antennas. A solution for the considered problem based on the Lagrangian method of multipliers (MoM) is presented, by formulating the precoder design as a constrained convex optimization problem. The obtained solution can be implemented in a fully distributed way among the SCs by using the preconditioned Richardson (PR) iteration. In numerical simulations, the convergence of the proposed DiP algorithm is verified and it is shown that the sum rate significantly increases, if the SCs cooperate with each other.